2014
DOI: 10.1155/2014/962043
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Theoretical Perspectives in Cognitive Science on the Presence of 1/f Scaling in Coordinated Physiological and Cognitive Processes

Abstract: Time series of human performances present fluctuations around a mean value. These fluctuations are typically considered as insignificant, and attributable to random noise. Over recent decades, it became clear that temporal fluctuations possess interesting properties, however, one of which the property of fractal 1/fscaling. 1/fscaling indicates that a measured process extends over a wide range of timescales, suggesting an assembly over multiple scales simultaneously. This paper reviews neurological, physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 129 publications
5
43
1
Order By: Relevance
“…For instance, alternative scaling methods could be used to examine 1/f noise such as detrended fluctuation analysis (DFA) or standardized dispersion analysis (SDA), which have been argued to yield more robust results with relatively short time-series data (Hasselman, 2013). Of more theoretical importance, however, we did consistently observe general patterns of 1/f noise in each of our conditions across both samples -successfully replicating general 1/f noise results observed in past research (Torre et al, 2011;Wijnants, 2014;Wijnants et al, 2012) and as originally observed in specific conditions of Correll's prior work (i.e., Correll, 2008, Study 1 and control condition of Study 2; Correll, 2011). Consequently, it is important to emphasize that though our results challenge Correll's (2008) theoretical account that 1/f noise in racial bias tasks reflects an effortful deliberative process, our results corroborate the fact that 1/f noise does indeed emerge in implicit racial bias tasks.…”
Section: Hardware Differencessupporting
confidence: 84%
See 1 more Smart Citation
“…For instance, alternative scaling methods could be used to examine 1/f noise such as detrended fluctuation analysis (DFA) or standardized dispersion analysis (SDA), which have been argued to yield more robust results with relatively short time-series data (Hasselman, 2013). Of more theoretical importance, however, we did consistently observe general patterns of 1/f noise in each of our conditions across both samples -successfully replicating general 1/f noise results observed in past research (Torre et al, 2011;Wijnants, 2014;Wijnants et al, 2012) and as originally observed in specific conditions of Correll's prior work (i.e., Correll, 2008, Study 1 and control condition of Study 2; Correll, 2011). Consequently, it is important to emphasize that though our results challenge Correll's (2008) theoretical account that 1/f noise in racial bias tasks reflects an effortful deliberative process, our results corroborate the fact that 1/f noise does indeed emerge in implicit racial bias tasks.…”
Section: Hardware Differencessupporting
confidence: 84%
“…Correll (2008) investigated the potentially meaningful fluctuations in RTs across trials using an approach referred to as 1/f noise, which refers to non-random patterns of long-range correlations that manifest as waves in the fluctuations of RTs over time (Gilden, 2001;Gilden, Thornton, & Mallon, 1995; but see Wagenmakers, van der Maas, & Farrell, 2012). In recent years, 1/f noise -also known as flicker noise or pink noise -has been documented in a wide number of biological and physical systems including the fluctuations in tide heights, heartbeat, and firings of single neurons (Gilden, 2001;Press, 1978; for a review see Wijnants, 2014). From this perspective, the sequence of raw RTs can be represented as a complex waveform which can be decomposed into simpler component waves via a Fast Fourier transform (FFT).…”
mentioning
confidence: 99%
“…The connection between fractals and human physiology was popularized to a large extent by publications in the American Physiological Society journals in the 1990s (16 -19, 21). In subsequent years, "fractal-based" analyses of output signals in physiology and behavior have developed in parallel on both sides of the Atlantic, in the U.S. (4,22,37,38) and in Europe (5,7,28,39). A major, must-read article has given scientific impetus to ongoing and emerging ideas in 2002 (12).…”
Section: Variability In Physiologymentioning
confidence: 99%
“…Any point in a fractal process, therefore, possesses the "dynamic memory" of all preceding points of the process and is therefore embedded in the historical context of the system Diniz et al, 2011). The presence of pink noise is also significant in that it indicates a balance between order and chaos (Wijnants, 2014), which characterizes healthy and well-coordinated systems (Herman, Giladi, Gurevich, & Hausdorff, 2005;. Indeed, pink noise lies on a continuum between white noise and Brown noise (see Figure 1), which we will describe below.…”
Section: Sse Variability As a Fractal Processmentioning
confidence: 99%
“…While the fractal properties of SSE across real time have not been examined to date, there is an abundance of evidence that real-time cognitive and motor processes reveal pink noise (for a review, see Wijnants, 2014). Moreover, there is rising evidence that pink noise is also displayed in socio-emotional processes, such as trial-by-trial reaction times in racial-bias tasks (Correll, 2008), short conversational storytelling sessions (Butner, Pasupathi, & Vallejos, 2008), and mood across the long term (from 1 to 2.5 years) (Gottschalk, Bauer, & Peter, 1995).…”
Section: Sse Variability As a Fractal Processmentioning
confidence: 99%